Unveiling Thesis Pursuit: Self-Efficacy's Resilience against Academic Anxiety: Membeberkan Penelusuran Tesis: Ketahanan Diri Terhadap Kecemasan Akademik - Zain , Nurisma Putri; Rusyid Affandi, Ghozali (Indonesian Journal of Education Methods Development, 2023)
This study addresses the pervasive issue of academic anxiety among undergraduates completing their theses, focusing on the Faculty of Psychology and Education at a prominent university. With a sample of 200 students, drawn using accidental sampling, the research explores the relationship between self-efficacy and academic anxiety. Self-efficacy was measured using a scale encompassing magnitude, strength, and generality, while academic anxiety was assessed through emotional, cognitive, and physical dimensions. Employing Rank Spearman correlation and SPSS 25.0, the analysis revealed a significant negative correlation (ρxy = -0.186, p < 0.05), underscoring the inverse connection between self-efficacy and academic anxiety during thesis work. These findings emphasize the potential of bolstering self-efficacy to mitigate academic anxiety, offering insights for educational institutions and practitioners to foster more confident and less anxious thesis pursuits. Highlights: Significant Relationship: The study uncovers a noteworthy negative relationship (ρxy = -0.186, p < 0.05) between self-efficacy and academic anxiety among students engaged in thesis work. Multi-Dimensional Assessment: Self-efficacy and academic anxiety were assessed through scales encompassing various dimensions, offering a comprehensive perspective on the interplay between these factors. Implications for Education: The findings underscore the potential of enhancing self-efficacy to alleviate academic anxiety during thesis pursuits, suggesting practical strategies for educational institutions to better support students in their research endeavors. Keywords: Academic anxiety, Self-efficacy, Thesis completion, Undergraduate students, Correlation.